Composition and Rheological Properties of Polysaccharide Extracted from Tamarind (Tamarindus indica L.) Seed - Shao, Huimin (Molecules, 2019)
A polysaccharide was extracted in high yield from tamarind (Tamarindus indica L.) seed (TSP) by acidic hot water extraction and ethanol precipitation. It was composed of 86.2% neutral polysaccharide, 5.4% uronic acid and 1.3% protein. The molecular weight of TSP was estimated to be about 1735 kDa, with glucose, xylose, and galactose in a molar ratio of 2.9:1.8:1.0 as the major monosaccharides. The steady shear and viscoelastic properties of TSP aqueous solutions were investigated by dynamic rheometry. Results revealed that TSP aqueous solution at a concentration above 0.5% (w/v) exhibited non-Newtonian shear-thinning behavior. Dynamic oscillatory analysis revealed that 10% (w/v) TSP showed as a “weak gel” structure. Apparent viscosities and viscoelastic parameters of TSP solutions decreased drastically in an alkaline solution of pH > 10, but slightly influenced by acidic solution, high temperature and the presence of salt ions and sucrose. These results indicated that TSP possessed excellent pH-resistance and thermo-stability, which might be suitable for applications in acidic beverages and high-temperature processed foodstuffs.